Programmable Hierarchical Kirigami: Programmable Hierarchical Kirigami (Adv. Funct. Mater. 6/2020). (5th February 2020) - An, Ning; Domel, August G.; Zhou, Jinxiong; Rafsanjani, Ahmad; Bertoldi, Katia
Abstract : In article number 1906711, Ahmad Rafsanjani, Katia Bertoldi, and co‐workers create kirigami metasurfaces comprising thin plastic sheets perforated with a hierarchical pattern of cuts arranged to form an array of hinged squares. By harnessing buckling instability, a variety of 3D deformation patterns can be triggered into these structures and the stress–strain response of the surface can be effectively programmed.